Possibility studies of using local cement in oil and gas wells cementing operation in Malaysia - Part III - Samsuri, Ariffin; Shahrudin, Shahrin; Suhaimi, Ahmad; Nasir, Abu Samah; Ahmad, Zainudin (1994)
Besides the chemical and normal physical properties evaluation neat cement must also show its compatibility towards additives when they are mixed with the additives and tested at reservoir condition. Retarder and fluid loss additive were mixed with the pfa and G cements at different percentage by cement weigth and their physical properties were studied by closely followed the API Specification 10 and were tested at simulated reservoir conditions. Results proved that locally produced blended cement is compatible for cementing job as compared to G cement.